A novel 4-aminoantipyrine-Pd(II) complex catalyzes Suzuki–Miyaura cross-coupling reactions of aryl halides - Contreras-Celedón, Claudia Araceli; Mendoza-Rayo, Darío; Rincón-Medina, José A.; Chacón-García, Luis (Beilstein Journal of Organic Chemistry, 2014)
A simple and efficient catalytic system based on a Pd complex of 4-aminoantipyrine, 4-AAP–Pd(II), was found to be highly active for Suzuki–Miyaura cross-coupling of aryl iodides and bromides with phenylboronic acids under mild reaction conditions. Good to excellent product yields from the cross-coupling reaction can be achieved when the reaction is carried out in ethanol, in the open air, using low loading of 4-AAP–Pd(II) as a precatalyst, and in the presence of aqueous K2CO3 as the base. A variety of functional groups are tolerated.
Keywords: 4-aminoantipyrine; arylboronic acids; biaryls; cross-coupling; palladium(II) complex